Study on Occupational Health Status of Secondary Level Teachers Teaching in Government School of Kathmandu District - Bhattarai, Prithutam; Bashistha, Mahesh; Acharya, Indra Prashad (Journal of Training and Development, 2019)
Introduction: Occupational health hazards of teaching includes ill health, poor physical posture and confusion that plays a vital role in triggering other diseases which are associated with musculoskeletal, cardiovascular, gastrointestinal, vocal cord, skin and other health problems. Most of the teachers develop occupational health problems after being enrolled into this profession, identification of such problems should be carried out in the initial phase of the profession. Objective: To access the health status of teachers in terms of age, gender, health problem and types of health problem. To access the association between gender, years in profession and health problem. Methodology: Cross-sectional study was conducted among teachers of selected secondary level Government school of Kathmandu i.e. 50 schools. Sample size of 270 was calculated. Random sampling was used for school selection. Response rate was 95.5 % i.e. 258 samples were collected. Result: Majority of the teachers i.e. 69% were facing some kind of health problem. Respondents who were above 30 years were found to have different kinds of health problems. Significant association between teaching for more than 10 years and health problem was observed among Males (72.7%, P<0.05) and females (82.5%, P< 0.05). Conclusion: The proportion of health problem was slightly higher among male teachers than in female teachers. It is necessary to improve the work standards and quality of life of teachers, through establishment of routine health checkups and strong coordination between District Education office and District Public Health office.